2021
DOI: 10.1001/jamanetworkopen.2021.28667
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Psychosocial Care Quality Improvement Strategy to Address Quality of Life in Patients With Cancer

Abstract: IMPORTANCEMany patients with cancer who would benefit from psychosocial care do not receive it. Implementation strategies may favor the integration of psychosocial care into practice and improve patient outcomes. OBJECTIVE To evaluate the effectiveness of the Humanization in Cancer Care (HuCare) Quality Improvement Strategy vs standard care as improvement of at least 1 of 2 domains (emotional or social function) of patient health-related quality of life at baseline and 3 months. A key secondary aim included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“… 41 The EPOCH trial 42 implemented a quality improvement program in 15 873 patients undergoing emergency open major abdominal surgery in the United Kingdom failed to improve survival. The PORSCH trial 43 implemented an algorithm for early recognition and detection of postoperative complications on postoperative outcomes in 1805 patients after pancreatic surgery in the Netherlands almost halved 90-day mortality The multicenter HuCare2 trial 44 successfully improved QOL in 762 patients with cancer in Italy (mostly breast cancer; 5% pancreatic cancer) by implementing a quality improvement strategy. This demonstrates that a large stepped-wedge design is feasible, but it is challenging to achieve desired clinical outcomes on a national scale.…”
Section: Discussionmentioning
confidence: 99%
“… 41 The EPOCH trial 42 implemented a quality improvement program in 15 873 patients undergoing emergency open major abdominal surgery in the United Kingdom failed to improve survival. The PORSCH trial 43 implemented an algorithm for early recognition and detection of postoperative complications on postoperative outcomes in 1805 patients after pancreatic surgery in the Netherlands almost halved 90-day mortality The multicenter HuCare2 trial 44 successfully improved QOL in 762 patients with cancer in Italy (mostly breast cancer; 5% pancreatic cancer) by implementing a quality improvement strategy. This demonstrates that a large stepped-wedge design is feasible, but it is challenging to achieve desired clinical outcomes on a national scale.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, psychological research in medical and oncological settings constantly increased focusing on observed outcomes of psychological care (Mannarini et al, 2013;Caminiti et al, 2017Caminiti et al, , 2021. In this context, the construct of psychological distress has rapidly gained popularity (Mitchell, 2010;Wise et al, 2013;Riba et al, 2019;Marconi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An observational research design was used to investigate the psychological distress experienced by oncological outpatients during the first few weeks between the diagnosis of cancer and the first psychological clinical session-in line with the procedure provided by the HuCARE study protocol (Passalacqua et al, 2016;Marconi et al, 2020;Caminiti et al, 2021;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meeting the psychosocial care needs of patients is essential for ensuring their optimal safety, recovery, and positive experiences [ 1 ]. Interventions improving psychosocial care, such as clinician communication training and on-site visits for context analysis and problem-solving, have been demonstrated to be effective to reduce suffering [ 2 ] and improve quality of life [ 3 ] in patients with dementia or cancer. Furthermore, the effectiveness of psychosocial techniques to decrease post-operative pain and improve perioperative clinical care in orthopedic surgery has been reported in a meta-analysis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%